Temni vzorci kot pravni problem - Skočir, Manja (Pravni letopis, 2025)
The article examines dark patterns as a manifestation of insights from behavioural economics in digital design, and as a legal issue that threatens user autonomy. The first part explains how dark patterns influence user decisions by exploiting cognitive biases, automated responses and the contextual framing of decision-making. Drawing on an analysis of existing literature, it traces the evolution of the concept from Brignull’s classification of deceptive practices to modern taxonomies that recognise dark patterns as multi-level influence mechanisms, frequently embedded within the architecture of digital systems. The second part focuses on the European Union’s legal responses, finding that regulation initially involved reinterpreting existing privacy and consumer protection mechanisms, but has since evolved to encompass the direct regulation of dark patterns. The analysis reveals that personal data protection law provides only limited protection, extending only to cases of manipulative consent, while consumer law provides a broader framework, albeit with the drawback of relying on the concept of the "average consumer", which does not accurately reflect real behavioural biases. New legislation, such as the Digital Services Act and the Artificial Intelligence Act, represents a significant shift towards safeguarding autonomy in digital decision-making processes. Thus, the article contributes to establishing a normative debate on dark patterns in the Slovenian context, advocating the need for a legal framework that recognises human cognitive vulnerability as the starting point for digital regulation, rather than relying on the information and consumer paradigms.
Keywords: arhitektura izbire; choice architecture; consumer protection law; dark patterns; data protection law; digital manipulation; digitalna manipulacija; pravo varstva potrošnikov; pravo varstva zasebnosti; temni vzorci